Administrasi Ruang Lingkup, Penyusunan Program, dan Format Program Kepala Sekolah - Fitratul Mubaraq; Awaluddin Hidayat; Maizal Efendi; Muhammad Alif Al Aziz; Sakban Sakban (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The aim of this research is to answer problems regarding the scope and preparation of the principal program implemented by Muhammadiyah Pekanbaru Elementary School 2. The curriculum improves quality, namely by applying new concepts in learning. Educational administration can be defined as a series of activities or the entire process of controlling the collaborative efforts of a number of people to achieve educational goals in a planned and systematic manner held in a certain environment, especially in the form of formal educational institutions. The method used in the research is qualitative, with a descriptive type of research and determining information using surveys as well as going into the field at the school by means of interviews, observation and documentation at SD MUHAMMADIYAH 2 school.